An Expert System for computer (hardware) diagnosis - Omar, Muhammad Fazdlie (2003)
This thesis discusses the key issues of development of an Expert System (ES) proposed for diagnosing the computer's hardware failure. This system used webbased environment for the computer's hardware self-assesment diagnosing so that its easier for the users to access at any convenient time. The basic development of the system is based on the concept of Engineering Knowledge Based Expert System approach. This knowledge based approach, is used to generate facts by using a set of rules to retrieve a solution. It will choose parts of the symptoms by referring to other relevant symptoms by using rule-based reasoning. The main activities in developing the system include the knowledge acquisition, knowledge validation, knowledge representation, inference and explanation. The system is independent as and instant expert help for any computer users to repair their own computer quickly.